Relationship between academic achievement and ners professional student anxiety in facing the nursing competence test in Medan 2022 - Br. Ginting , Friska Sri Handayani; Siallagan, Ance M.; Gulo , Lely Kurnia (International Journal of Nursing and Midwifery Research, 2023)
Anxiety is a term that is very familiar with everyday life which describes a state of worry, anxiety, fear, restlessness accompanied by various physical complaints. Nurse profession students often experience anxiety when facing exams, especially when facing competency tests because competency tests are one of the requirements to be declared graduated from education and are entitled to a registration certificate (STR). The purpose of this study was to determine the relationship between academic achievement and the anxiety of nursing professional students in facing the nursing competency test in the field in 2022. The research design used in this study was a correlation research design using the cross sectional method. The instruments used in data collection are questionnaire sheets and observation sheets. The results of the Spearman Rank statistical test P = 0.047 (p> 0.05) showed that there was no relationship between academic achievement and the anxiety of nursing professional students in facing the nursing competency test in the field in 2022. It is recommended for further researchers to identify other factors that affect the anxiety of professional students nurses in facing the competency test.